1992
DOI: 10.1007/bf00132751
|View full text |Cite
|
Sign up to set email alerts
|

Comments on hematogenous metastatic patterns in humans as revealed by autopsy

Abstract: An attempt is made to clarify some general concepts of hematogenous metastatic patterns in humans, by the use of autopsy data. The significance and problems associated with 'false negative' reports are assessed. By the use of metastatic efficiency indices in which the incidence of specific target organ involvement is related to organ blood-flow, 'seed-and-soil' effects are discriminated from the effects of differential cancer cell delivery. An analysis of autopsy data from cases with a history of colorectal ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
115
0
3

Year Published

1993
1993
2009
2009

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 175 publications
(118 citation statements)
references
References 17 publications
0
115
0
3
Order By: Relevance
“…The extent of metastasis measured in spontaneous versus experimental metastasis assays can provide insights into mechanisms of host compartment-mediated influence on metastasis (15,(18)(19)(20)(21)(22)(23). For example, in models where primary tumor growth is unchanged between treatment groups, i.v.…”
Section: Discussionmentioning
confidence: 99%
“…The extent of metastasis measured in spontaneous versus experimental metastasis assays can provide insights into mechanisms of host compartment-mediated influence on metastasis (15,(18)(19)(20)(21)(22)(23). For example, in models where primary tumor growth is unchanged between treatment groups, i.v.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical and preclinical data have shown that primary tumors disseminate to selective secondary organs, which cannot solely be explained by the anatomic distribution of the blood flow to the various organs (22). Whereas breast cancer has a predilection for the skeleton, uveal melanoma and colon cancer preferentially spread to liver (reviewed in refs.…”
Section: Introductionmentioning
confidence: 99%
“…These have all been relatively small-scale studies (Abrams et al, 1950;Weiss et al, 1988;Weiss, 1992;Disibio and French, 2008). However, we may now study these patterns using computational methods on large data sets.…”
mentioning
confidence: 99%